Mental disorders in Malaysia: an increase in lifetime prevalence. (November 2021) - Raaj, Shaeraine; Navanathan, Sujesha; Tharmaselan, Myelone; Lally, John
Abstract : There is an increasing prevalence of mental disorders in Malaysia, with a growing need to improve access to timely and efficient mental healthcare to address this burden. This review outlines the current legislative framework and the challenges of delivering mental healthcare and treating mental disorders in Malaysia.